Processes of Immigration in Rural Europe. The Status Quo, Implications and Development Strategies - Kordel, Stefan; Weidinger, Tobias; Jelen, Igor (Cambridge Scholars, 2018)
Contemporary immigration processes, e.g. forced migration and labour induced mobility as well as lifestyle and leisure oriented movements increasingly affect areas in Europe that are considered as peripheral or rural. This edited collection sheds light to the diversity of in-migration, their specific implications for development and strategies to cope with. Contributions from various sub-disciplines of the social sciences, e.g., human and cultural geography, sociology and spatial planning with different regional foci, aim at encouraging theoretical discussions, enhancing empirical knowledge and providing stimuli for practitioners involved in migration and development issues. The structure of the volume therefore follows four main themes: (1) conceptual reflections on immigration to peripheral rural areas and development prospects; (2) patterns and types of immigration processes, drawing on various case studies from all over Europe; (3) realms of integration, i.e., housing, economy and social life; (4) immigration management with a special emphasis to regional and local strategies, undertaken by policy-makers, the private sector and civil society.